Mechanical Activation of Hypoxia-Inducible Factor 1α Drives Endothelial Dysfunction at Atheroprone Sites. Issue 11 (November 2017) - Feng, Shuang; Bowden, Neil; Fragiadaki, Maria; Souilhol, Celine; Hsiao, Sarah; Mahmoud, Marwa; Allen, Scott; Pirri, Daniela; Ayllon, Blanca Tardajos; Akhtar, Shamima; Thompson, A.A. Roger; Jo, Hanjoong; et al.
Abstract : Objective—: Atherosclerosis develops near branches and bends of arteries that are exposed to low shear stress (mechanical drag). These sites are characterized by excessive endothelial cell (EC) proliferation and inflammation that promote lesion initiation. The transcription factor HIF1α (hypoxia-inducible factor 1α) is canonically activated by hypoxia and has a role in plaque neovascularization. We studied the influence of shear stress on HIF1α activation and the contribution of this noncanonical pathway to lesion initiation. Approach and Results—: Quantitative polymerase chain reaction and en face staining revealed that HIF1α was expressed preferentially at low shear stress regions of porcine and murine arteries. Low shear stress induced HIF1α in cultured EC in the presence of atmospheric oxygen. The mechanism involves the transcription factor nuclear factor-κB that induced HIF1α transcripts and induction of the deubiquitinating enzyme Cezanne that stabilized HIF1α protein. Gene silencing revealed that HIF1α enhanced proliferation and inflammatory activation in EC exposed to low shear stress via induction of glycolysis enzymes. We validated this observation by imposing low shear stress in murine carotid arteries (partial ligation) that upregulated the expression of HIF1α, glycolysis enzymes, and inflammatory genes and enhanced EC proliferation. EC-specific genetic deletion of HIF1α in hypercholesterolemic apolipoprotein E–defecient mice reduced inflammation and endothelial proliferation in partially ligated arteries, indicating that HIF1α drives inflammation and vascular dysfunction at low shear stress regions. Conclusions—: Mechanical low shear stress activates HIF1α at atheroprone regions of arteries via nuclear factor-κB and Cezanne. HIF1α promotes atherosclerosis initiation at these sites by inducing excessive EC proliferation and inflammation via the induction of glycolysis enzymes. Abstract : Supplemental Digital Content is available in the text.